DAYA TERIMA BISKUIT TINGGI PROTEIN DENGAN PENAMBAHAN TEPUNG BIJI DURIAN (HIGH PROTEIN BISCUITS RECEIVED POWER WITH THE ADDITION OF DURIAN SEED FLOUR) - Besti Verawati; Nopri Yanto (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2018)
Biscuits are one snack or snack that is consumed by people in Indonesia. Thepurpose of this research is the utilization of flour in making durian bij biscuits.This research is experimental design using Draft. This research is experimentaldesign using a complete Randomized Design (RAL) non factorial that iscomposed only of one factor, namely biscuit selected formulations with thesymbol BF all of which are repeated as many as 3 times (i = 1, 2, 3). Testanalysis of the difference of using test ANOVA and Duncan test information.Panelists are somewhat trained 25 people i.e. students Undergraduate Universitynutrition status of Hero Tuanku Tambusai. There is no difference in the additionof durian seed flour flavor, color, and aroma biscuits. There is a difference theaddition of durian seed flour against texture. Based on further testing of Duncan,the texture of the cookies is no different. Test results hedonik, formula biscuitsmost-favored by panelists is formula F2. durian seed flour addition seanyak 20%.